Microsoft SQL Server 2005 administrator's companion - Whalen, Edward (Microsoft Press, 2006)
Get comprehensive information to plan, deploy, administer, and support Microsoft SQL Server 2005 in organizations of any size. With the ADMINISTRATOR'S COMPANION, you get mission-critical information in a single volume - straight from the experts.